Engineering Ethics Case Study of Hydroelectric Sayano- Sheshenkaya Accident: Lesson Learned for Malaysian Engineer - Sulaima, Mohamad Fani; Othman, Md Nazri; Jali, Mohd Hafiz; Nor, Mohd Khanapiah; Shamsudin, Nur Hazahsha (Journal of Technology, 2014)
Sayano–Shushenskaya hydroelectric power station can be categorized as the biggest hydro power plant in Russia. The power plant full capacity is 6500MW. It is made up of 10 turbines which is each turbine rated power is 650MW. The accident that happened in the power station have been claimed many lives and high cost of damage. All people are keeping asking about the main causes of this tragedy. In order to know the causes of this tragedy, a study case needs to be conducted in order to relate the study with the engineering ethical theory. The goal of this case study is to study about the main causes of the accident that is related with the code of ethics and find the lessons that can be taken from the accident toward Malaysian engineer. This case study shows most of the causes of the accidents are related to the engineering ethical theory. The results of the findings really indicate the important of following the code of ethics in the working environment. The safety of the hydro plant resources is depending on the people who are conducting the plant in a proper manner.